Inovasi Pembelajaran Keterampilan Menulis Iklan Melalui Media Audio Visual Di SMP Negeri 27 Padang - Ria Satini; Zulfitriyani; Titiek Fujita Yusandra (Kilau Publishing, 2025)
This community service was carried out to improve the advertising writing skills of eighth-grade students of SMP Negeri 27 Padang. The training was conducted using audio and visuals, as an approach believed to motivate students' creativity. In this digital era that prioritizes the speed of information, the ability to construct persuasive messages through advertising has become a skill that cannot be ignored. Initial observations at SMP Negeri 27 Padang showed a challenge: many students still had difficulty composing words and developing ideas for advertising, while the learning methods often used seemed ineffective. The research method used was a qualitative method with descriptive analysis techniques. The participants involved were 32 eighth-grade students who took part in the advertising text writing lesson. The results obtained from this training were students able to write advertising texts more creatively. Student motivation in learning increased and students' ability to develop ideas in writing advertising texts became better and more structured.